Advanced imaging in colonoscopy: contemporary approach to dysplasia surveillance in inflammatory bowel disease. Issue 4 (23rd August 2016) - Beintaris, Iosif; Rutter, Matt
Abstract : Inflammatory bowel disease (IBD) (ulcerative colitis (UC) and Crohn's disease (CD)) is a chronic relapsing/remitting condition characterised by intestinal inflammation. One of the main concerns in patients with longstanding ulcerative and Crohn's colitis is development of colonic dysplasia and colorectal cancer (CRC), a risk higher than that of the general population. Colonoscopy surveillance programmes have been developed by major societies worldwide to improve early dysplasia detection and treatment, thus preventing progression to colorectal cancer. Colonoscopy is an imperfect tool as lesions can be missed, an issue even more relevant to colitic patients, where mucosal inspection and lesion recognition may prove challenging. Extensive research has been undertaken on performance improvement in this area while technical advances in optical imaging, such as high-definition, have made their way into modern endoscopy units. Techniques and technologies available to enhance optical diagnosis of dysplasia in inflammatory bowel disease are reviewed in this paper, focusing on those that are realistic, widely available and feasible for everyday practice.